Buddhist Cultural Heritage of Lo Manthang and Satellite Settlements, Mustang, Nepal - Regmi, Umesh (Literary Studies, 2024)
This paper reads upper Mustang area from the cultural perspective. While doing so it excavates the history of the area and its people’s cultural practices for their identity. The ethnic community copes with adverse natural adversity and embedded with the land. Apparently historicity refers the past events happened on the people and places in the course of time. It mainly focuses on the actors who caused the events happen and the consequences of the actions either political or economical or social or cultural facets of the society. This paper primarily reads Mustang and her people how they lived, practised the culture and sustained their independent identity fighting with the fair and adverse weather. The world is under the influence of identity politics. People whether locals or immigrants are raising the voice for their sovereign identity that establishes the social and cultural recognition of the people. The language, culture, social mores, lodging style and food stuffs consumed by locals as well as clothing style set up the identity of the people. In Mustang area most of the people save the government personnel's have the same way of life and language which denotes the formation of ethnic community.